2016
DOI: 10.1074/jbc.m116.737353
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Glutamatergic Synaptic Activity Regulates Constitutive COX-2 Expression in Neurons OPPOSING ROLES FOR THE TRANSCRIPTION FACTORS CREB (cAMP RESPONSE ELEMENT BINDING) PROTEIN AND Sp1 (STIMULATORY PROTEIN-1)

Abstract: Edited by Paul E. FraserBurgeoning evidence supports a role for cyclooxygenase metabolites in regulating membrane excitability in various forms of synaptic plasticity. Two cyclooxygenases, COX-1 and COX-2, catalyze the initial step in the metabolism of arachidonic acid to prostaglandins. COX-2 is generally considered inducible, but in glutamatergic neurons in some brain regions, including the cerebral cortex, it is constitutively expressed. However, the transcriptional mechanisms by which this occurs have not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 77 publications
1
6
0
Order By: Relevance
“…GluN1 transgenic mice were shown to report increases in proliferating neural progenitor cells in the adult sugranular zone of dentate gyrus (41), whereas GluN2A KO mice were described to present better exercise-induced amelioration of proliferating neural progenitor cells compared to WT mice (42). In addition, GluN1 null mutant embryo, COX-2 mRNA expression was significantly decreased compared to that in the wide-type embryo (43). Therefore, the reduction in GluN1 and GluN2A/2B observed in COX-2 KO mice may be closely associated with decreases in both the proliferating activity and synaptic plasticity.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…GluN1 transgenic mice were shown to report increases in proliferating neural progenitor cells in the adult sugranular zone of dentate gyrus (41), whereas GluN2A KO mice were described to present better exercise-induced amelioration of proliferating neural progenitor cells compared to WT mice (42). In addition, GluN1 null mutant embryo, COX-2 mRNA expression was significantly decreased compared to that in the wide-type embryo (43). Therefore, the reduction in GluN1 and GluN2A/2B observed in COX-2 KO mice may be closely associated with decreases in both the proliferating activity and synaptic plasticity.…”
Section: Discussionmentioning
confidence: 86%
“…This result is consistent with a previous study indicating that genetic and pharmacological inhibition of COX-2 prominently decreased the number of pCREB-immunoreactive nuclei in the dentate gyrus (1719). In addition, luciferase assay demonstrated that CREB was involved in the constitutive expression of COX-2 in neurons (43).…”
Section: Discussionmentioning
confidence: 99%
“…Murray and O’Connor ( 2003 ) reported that cyclooxygenase-2 (COX-2), an enzyme synthesizing prostaglandins involved in inflammatory processes, inhibits long-term potentiation (LTP) in rat dentate gyrus, pointing to COX-2 role in memory and learning. COX-2 was found to be constitutively expressed in both cortical and hippocampal neurons (Yamagata et al 1993 ) and being dependent on N -methyl-D-aspartate (NMDA) receptor activity (Hewett et al 2016 ). The expression of COX-2 could be markedly increased in astroglia and microglia in the presence of inflammatory stimuli (Font-Nieves et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Neuronal expression is coupled to endogenous postsynaptic N-Methyl-D-Aspartate type glutamate receptor (NMDAR) activity and as such, can be modified by changes in excitatory neuronal activity. In this regard, antagonism of the NMDAR or deletion of its gene suppresses basal COX-2 mRNA expression by cortical neurons both in the brain and in culture (Yamagata et al, 1993; Hewett et al, 2016). Moreover, neuronal COX-2 mRNA and protein expression in the brain are upregulated strongly in response to excitatory stimulation (Yamagata et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…While the regulation of COX-2 expression has been studied extensively in non-neuronal cell types, much less is known about its regulation in neurons. Numerous transcriptional regulatory proteins are known to bind to cis -acting elements in the 5′ regulatory region of the COX-2 gene and recent evidence from cultures of cortical neurons indicates that basal COX-2 expression is modulated transcriptionally by both Cyclic AMP Response Element Binding protein and Sp-1 (Hewett et al, 2016). The 3′ untranslated region (3′UTR) ofCOX-2 mRNA is a second regulatory region that has the capacity to bind numerous RNA binding proteins (RBPs), which can affect stability and/or translation of the transcript (Dixon et al, 2000).…”
Section: Introductionmentioning
confidence: 99%